Eksplorasi Tumbuhan Obat Hutan Berkhasiat Inhibitor HMG-KoA Reduktase (Exploration of Medicinal Forest Plants with HMG-CoA Reductase Inhibitory Activity) - Sulistiyani Sulistiyani; Rita K Sari; Wulan Triwahyuni (Masyarakat Peneliti Kayu Indonesia, 2017)
Five medicinal forest plants are potential candidates to be developed as cholesterol-reducing herbal product. The objective of this research is to explore the potency of the leaf of pulai ((Alstonia scholaris, R.Br), jabon merah (Antocephalus macrophyllus), jati belanda (Guazuma ulmifolia), mindi (Melia azedarach), and surian (Toona sinensis) based on their main secondary metabolic contents and to study their activity as HMG-CoA reductase inhibitor, an enzyme key in the regulation of cholesterol biosynthesis. Dried leaves materials were prepared from the each plant by standard procedure and their pythochemicals contents were determined qualitatively. Subsequently, flavonoid fractions from the leaves of all five plants were prepared, and alkaloid fraction was prepared from the leaf of pulai only. The flavonoid content was determined using quercetin as standard. The effect of each samples on the HMG-CoA reductase activity were analyzed using HMGR in vitro assay kit. At concentration of 20 ppm jati belanda leaf extract, however, showed the highest inhibitory activity which was similar to quercetin (5 ppm) as well as pravastatin control inhibitor. Further analysis showed that extracts from leaves of all plants tested were shown to inhibit the HMG-CoA reductase with IC50 values ranging from 7.53 to 52.62 ppm.Keywords: HMG-KoA reductase inhibitor, in vitro assay, medicinal forest plant exploration